Detection and characterisation of delamination damage propagation in Woven Glass Fibre Reinforced Polymer Composite using thermoelastic response mapping. (1st October 2016) - Kakei, Ayad; Epaarachchi, J.A.; Islam, Mainul; Leng, J.; Rajic, N.
Abstract: This paper details a study on the application of Thermoelastic Stress Analysis (TSA) for the investigation of delamination damage propagation in glass fibre reinforced composite materials. A woven Glass (0/90)/Epoxy composite sample containing a purposely created delamination was subjected to a step-cyclic loading (varying mean level) whilst monitoring the thermoelastic response of the sample with an infrared camera. A finite element analysis (FEA) was performed using cohesive elements to simulate the propagation of the delamination under a monotonically increasing axial load. It is shown that the delamination crack length inferred from the TSA results is consistent with microscopic analysis of the sample, and that the measured crack growth rate is in reasonable agreement with simulation results.